Pengaruh Earning Per Share, Price To Book Value dan Net Profit Margin Terhadap Harga Saham Perusahaan Transportasi yang Terdaftar di BEI Tahun 2016 – 2018 - Ma'rifatul Hayyinah; Renny Augustina (Fakultas Ekonomi Universitas Panca Marga, 2020)
Abstract: This research was conducted to test the influence of Earning Per Share, Price to Book Value, and Net Profit Margin on stock prices in transportation companies listed on the IDX in 2016 - 2018. The type of research used is causal research. Data collection method with documentation. From a total population of 34 companies, a sample of 29 transportation companies listed on the IDX was obtained, using purposive sampling technique. The data analysis method is multiple linear regression analysis. The results showed that Earning Per Share, Price to Book Value, and Net Profit Margin had a significant influence on the variable Share Price in transportation companies listed on the IDX in 2016 - 2018. Keywords: Earning Per Share, Net Profit Margin, Price to Book Value, Stock Price